Effects of harvest period, storage, and genotype on postharvest physiological deterioration responses in cassava (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rahmawati RK, Khumaida N, Ardie SW, Sukma D, Sudarso. 2021. Effects of harvest period, storage, and genotype on postharvest physiological deterioration responses in cassava. Biodiversitas 23: 100-109. Postharvest physiological deterioration (PPD) is the major constraint in cassava root production. The breeding program to develop PPD tolerant cassava varieties requires a long period to complete. Although it is the first step in breeding for PPD tolerance, evaluating cassava germplasm responses for the PPD remains a major problem because it is a laborious process, and the evaluation often contains a high experimental error. This study aims to develop methods for evaluating PPD response, i.e., evaluating the effects of two harvest periods and storage on PPD responses of nine cassava genotypes. The developed scoring system based on cassava root discoloration could group the evaluated cassava genotypes into either PPD tolerant, medium tolerant, or sensitive. The tolerant varieties showed less than 10% root discoloration areas, while the medium tolerant was between 11-20%, and the sensitive was larger than 20%, respectively. ADR-24 and GJ-11 were identified as PPD tolerant, while ML-19 was sensitive using the developed scoring system. This study showed that PPD is a complex phenomenon associated with genetics and environmental factors. Root dry matter content and maximum root diameter traits may play an important role in PPD development in cassava. We have developed procedures for identifying genotype responses to PPD and showed that cassava roots harvested as early as eight months after planting and stored as late as five days under the control relative humidity were good conditions for studying PPD. Evaluating the percentages of root discoloration was a good measure for PPD response prediction. Moreover, we showed that less than 10%, 20%, and more than 20% of root discoloration might be used to group cassava into PPD tolerant, medium tolerant, and sensitive for Indonesian accessions. Therefore, the methods developed in this study may support the Indonesian cassava breeding program and provide biochemical and molecular analysis materials to elaborate the mechanisms of PPD in cassava roots.
Keywords: Dry matter content; PPD; Storage roots; Shelf life; Manihot esculenta